MODEL OF DYNAMIC ELEVATOR CONTROL SYSTEM USING CENTRAL APPLICATION SERVER - Furgała, Łukasz; Kolano, Krzysztof; Mosorow, Włodzimierz (Informatyka, Automatyka, Pomiary w Gospodarce i Ochronie Środowiska, 2017)
The passenger handling process of personal passenger lifts usually implements local microprocessor devices. This solution has significant limitations. Among them, you can mention low computing power CPU, the need to install each time on each microcontrollers in the case of a new software version. Data acquisition requires costly modules to record and access historical data. More optimal handling of the elevator or group of lifts can be achieved by the proposed transfer of the control algorithm to the central server. The solution based on the proposed model will also allow you to remote configuration, management of parameters, including dynamic change of control algorithm and advanced management access and permissions.